Asia Pacific Regional Cooperation and integration index enhanced framework, analysis, and applications. - Kim, Sung Su; Sonn, Jung Won (Asian Development Bank, 2021)
This report discusses the enhanced framework of the Asia Pacific Regional Cooperation and Integration Index (ARCII) that now includes digital connectivity and environmental cooperation among other innovations for monitoring progress.